The Role of Blockchain Technology in Addressing Business Fraud - Qinta Berliana Valfini (Generate Digital Publishing, 2025)
Objective: This research explores the role of blockchain technology in addressing fraud in the food supply chain, with a focus on IBM Food Trust. The main objective is to evaluate how blockchain improves transparency, traceability and auditability across the supply chain, as well as its impact in reducing fraud and increasing consumer confidence. Research Design & Methods: The methodology used was a qualitative case study, centered on the IBM Food Trust as the main platform. Data was collected through document analysis of relevant literature, annual reports, and case studies. Secondary sources, such as research papers and reports on blockchain implementation in the supply chain, using a comprehensive approach. Findings: The research highlights that blockchain significantly reduces the time needed to track products, increases transparency, and minimizes the risk of fraud by providing an immutable record of transactions. In the case of IBM Food Trust, the time to trace products such as mangoes was reduced from days to seconds. In addition, consumers reported increased confidence in food safety and product quality due to the traceability features provided by blockchain technology. Implications: The results indicate that blockchain technology could transform the food supply chain by enhancing efficiency, minimizing fraud, and promoting transparency. Nonetheless, achieving successful adoption necessitates addressing challenges like integration with current systems, substantial initial costs, and the requirement for stakeholder education and training. Contribution: This research contributes to the growing body of knowledge on the application of blockchain in supply chain management. The research provides practical insights into the benefits and challenges of blockchain implementation, particularly in the food industry, and highlights its potential to drive greater transparency, trust, and operational efficiency.